Quality-of-life survey of pancreatic cancer patients: a comparison between general public and physicians - Sasahara, Yuriko; Takumoto, Yuki; Watanabe, Kaname; Takeda, Hiroyuki; Umemoto, Kumiko; Sunakawa, Yu; Suzuki, Naoki; Yoshioka, Takashi; Kobayashi, Satoshi; Ueno, Makoto; Nakamura, Sho; Akazawa, Manabu; et al. (Frontiers in Health Services, 2024)
BackgroundQuality-of-life (QOL) is important for cancer patients with poor prognosis. However, conducting a QOL survey with patients is difficult. Therefore, we conducted a QOL survey with physicians. Specifically, this study aimed to clarify how physicians assess QOL in patients with pancreatic cancer by conducting a survey and comparing the results between physicians and the general public.MethodsA survey was conducted by interviewing physicians administering chemotherapy to patients for recurrent/metastatic pancreatic cancer. This method is similar to that of the QOL survey conducted among the general public. Responses were evaluated using the composite time trade-off (cTTO) and the visual analog scale (VAS) for 11 pancreatic cancer status scenarios (survey scenarios). These scenarios consisted of patients’ health states as well as the types and grades of adverse events (AEs). Health status was classified into two categories: Stable disease (SD) and Progressive disease (PD). In addition, we conducted a survey using the EuroQol 5 Dimensions 5-Level (EQ-5D-5l) as reference values.ResultsTwenty physicians responded to the survey. SD had the highest mean QOL value for both assessment methods (Physicians: 0.78, General public: 0.63), whereas PD had the lowest mean QOL value (Physicians: 0.15, General public: −0.12). The physicians assigned higher QOL values on both the VAS and cTTO than the general public did in all survey scenarios.ConclusionsThe QOL values obtained from physicians were consistent with the degree of status in any assessment scenarios. Based on the differences in the QOL survey results between physicians and the general public, physicians tended to assign higher QOL values than the general public in cTTO and VAS assessments.